The Problem-Solving Skills Profile of Tsanawiyah Islamic School Students in the Vibration, Wave, and Sound Learning Materials - Mercury Nirwana; Mohamad Nur; Budi Jatmiko (IJORER : International Journal of Recent Educational Research, 2021)
The purpose of this study is to determine the profile of problem-solving instruments which applied in Tsanawiyah Islamic School on vibration, waves, and sound learning materials based on the expert validation assessment and student’s responses. This study used a pre-experimental design method, namely a one-shot case study and it was implemented in Tsanawiyah Islamic School. The sampling technique used purposive sampling using one class. Data collections used problem-solving skills instrument. The expert validation results showed that all of the instrument tests were very valid and it was declared fit for use. Student’s responses from 15 questions were valid because the instrument tests have difficulty level with medium category, although there was one number of the question has difficult category. The distinguishing power showed a good and a very good category although two numbers of questions were less categories. The problem-solving skills profile in Tsanawiyah Islamic School showed a good category in the expert validation noralthough student’s responses although there was a shortage. The limitation of the profile problem solving skills was hindsight from expert validation and students responses. The future research must be better and it can use appropriate learning model for this research like Model SEA-MEA (Self Efficacy Academic-Means Ends Analysis).